Mathesius's Study of the Subject-Verb Relation from A Dual Perspective - Li, Xiaojie; Han, Zhengtao (Journal of Theory and Practice in Linguistics, 2024)
After conducting an exhaustive study and comprehensive comparison of the sections dealing with verbs and subjects in Mathesius’s linguistic characterology, this paper contends that his approach to the subject-verb relationship incorporates two distinct perspectives. Through meticulous analysis, this study asserts that Mathesius’s interpretation of the subject-verb relation not only adopts the verb-centric perspective, emphasizing the sentence’s argument structure, but also embraces the subject-centric perspective, highlighting the information structure of the utterance. This dual focus not only illuminates the disparity between sentence potential and actualized utterance but also underscores one of the fundamental principles of Mathesius’s functional linguistics: adopting the speaker’s perspective in linguistic analysis.